What Do Banks, Rural Credit Institutions, and Regulators Infer from the Current Strengths and Standing of Indonesian SMEs? - Panjaitan, Jenri; Darwin, Muhadjir; Bastian, Indra; Sukamdi, Sukamdi (Gadjah Mada International Journal of Business, 2020)
This study investigates whether the Indonesian regulators control Indonesian small and medium-sized enterprises (SMEs) with matching or mismatching empowerment strategies, in light of their strengths and current standing. Indonesian SMEs contributed approximately 60.34% to Indonesia’s gross domestic product (GDP) in 2018. In addition, Indonesian regulators have focused on financial support through credit policies and tax incentives. Indonesian SMEs have been standing on organizational readiness and readiness for change, based on their social networks and social cognition. It collected thirteen informants with different expertise and experiences. This study’s results suggest Indonesia’s regulatory body and financial institutions should consider the SMEs’ social cognition and organizational readiness for change. According to the current situation, to empower Indonesian SMEs, we recommend strategies such as achieving knowledge supremacy, creating an economic development board, as in Singapore, formulating comprehensive industry-wide policies, adopting omnibus laws, and implementing a shifting balance strategy. In other words, the Indonesian regulators should implement major reforms, which are similar to glasnost and perestroika in the former Soviet Union. This is to enhance Indonesian SMEs and achieve the goal of the Government of Indonesia (GoI) with respect to the optimal distinctiveness of Indonesia’s future economy. This optimal distinctiveness refers to the GoI’s policies, which focused on knowledge supremacy, an industry-wide regime, and research for empowerment.